2017
DOI: 10.1213/ane.0000000000001675
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented Sleep Enhances Postoperative Neuroinflammation but Not Cognitive Dysfunction

Abstract: BACKGROUND: Sleep is integral to biologic function, and sleep disruption can result in both physiological and psychologic dysfunction including cognitive decline. Surgery activates the innate immune system, inducing neuroinflammatory changes that interfere with cognition. Because surgical patients with sleep disorders have an increased likelihood of exhibiting postoperative delirium, an acute form of cognitive decline, we investigated the contribution of perioperative sleep fragmentation (SF) to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 38 publications
(37 reference statements)
2
23
0
1
Order By: Relevance
“…We agree with the correspondents’ concern that we did not exhaustively assess memory paradigms, but we stated this caveat in the opening paragraph in the Discussion section of our report 4 .…”
supporting
confidence: 81%
“…We agree with the correspondents’ concern that we did not exhaustively assess memory paradigms, but we stated this caveat in the opening paragraph in the Discussion section of our report 4 .…”
supporting
confidence: 81%
“…Individuals with insomnia showed significantly reduced values of mean (a) and axial (b) diffusivity (FWE corrected p value < 0.05), and a trend for radial diffusivity (c) (FWE corrected p value between 0.05 and 0.1), compared with normal sleepers. L, left hemisphere; R, right hemisphere microglial activation in mouse brains [78,79]. An alternative explanation is that our results could have been driven by a hypothetical higher prevalence of preclinical AD among individuals with insomnia, as decreased MD in white matter has been previously associated with early β-amyloid deposition [80].…”
Section: Discussionmentioning
confidence: 88%
“…In NOR, a decline in short term visual recognition memory after tibial surgery is shown. Evidence is accumulating that NOR-related memory can be affected by different types of surgical trauma, such as abdominal surgery with upper mesenteric artery clamped (Hovens et al, 2014), or laparotomy (Kawano et al, 2015), and tibial fracture surgery (Vacas et al, 2017). Also, in the FC test, contextual-dependent memory was impaired after anesthesia/surgery as demonstrated by Terrando et al (2010Terrando et al ( , 2011, which was found in the learning phase.…”
Section: Discussionmentioning
confidence: 99%